(untitled) (Proceedings of Southern Federal University. Philology, 2014)
The article refers to “Blindsight”, a novel by the Canadian speculative fiction writer Peter Watts, to determine how the metaphor of the prosthesis influences personal identity. Prosthetic extensions reconfigure the shape of both the body and the personality, depriving the latter of the stable ground for (self) identification. The owner of a prosthetic identity is forced by the ‘Uncanny valley’ effect to search for new ways to evoke empathy in others and to strive for recognition of his right to subjective autonomy. Keywords: identity, prosthesis, Uncanny valley, consciousness, mediation, alienation. Author: Ananyina O.A.